A Morphometric Examination of Tibial Tuberosity in North Indian Population - Mohammad Rehan Asad (Journal of Pharmacy and Bioallied Sciences)
Background: Determining the morphometry and prominence of the tibial tuberosity was the primary goal of the current investigation. Tibial tuberosity morphometric data may be utilized to direct therapy and track the results of total knee replacement surgery. As a tractional apophysis, the tibial tuberosity may be the location of repeated avulsion fractures. Material and Methods: Fifty (35 right and 35 left) completely ossified dry tibiae of unknown sex were obtained from the Department of Anatomy for the current investigation. A Vernier caliper was used to collect morphometric measurements of the tibial tuberosity. A statistical study was conducted on the parameters. Result: It was determined that the right side’s lower rough section of the tibial tuberosity measured 47.77 ± 6.08 mm (range = 35.6-52.8 mm) and 46.84 ± 6.12 mm (range = 37.3-56.3 mm). The bottom rough portion of the tibial tuberosity measured 47.30 ± 5.97 mm in total. Although the difference between the two sides was statistically insignificant (P = .729), it was found to be greater on the left. The length of the lower rough portion of the tibial tuberosity on both sides was greater in the North Indian population when comparing the lengths of the top smooth and lower rough parts. Conclusion: Anatomists, orthopedicians, radiologists, rehabilitation experts, and sports medicine professionals will find the study’s findings useful in assessing anterior knee pain syndrome.